2021
DOI: 10.3390/jmse9020183
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Marine Coastal Litters around Zhoushan Island, China and Their Impacts

Abstract: Rapid development of the economy increased marine litter around Zhoushan Island. Social-ecological scenario studies can help to develop strategies to adapt to such change. To investigate the present situation of marine litter pollution, a stratified random sampling (StRS) method was applied to survey the distribution of marine coastal litters around Zhoushan Island. A univariate analysis of variance was conducted to access the amount of litter in different landforms that include mudflats, artificial and rocky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…In overall, the litter density ranged from 2.19 items/m 2 to 14.18 items/m 2 with a mean of 6.25 items/m 2 . These results are higher than the value obtained at the Columbian Central Caribbean Beaches (5.11 items/m 2 ), the Zhoushan Island, and the Adriatic and Ionian Beaches (0.67 items/m 2 ) by Rangel-Buitrago et al [ 55 ], Ma et al [ 54 ], and Vlachogianni et al [ 60 ] respectively. Perez-Venegas et al [ 58 ] recorded a litter density of 0.001 items/m 2 on Guafo Island (Chile) while Duhec et al [ 27 ] reported 4.7 items/m 2 on Alphonse Island (Seychelles), and 3.3 items/100 m 2 was recorded by Melli et al [ 61 ].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In overall, the litter density ranged from 2.19 items/m 2 to 14.18 items/m 2 with a mean of 6.25 items/m 2 . These results are higher than the value obtained at the Columbian Central Caribbean Beaches (5.11 items/m 2 ), the Zhoushan Island, and the Adriatic and Ionian Beaches (0.67 items/m 2 ) by Rangel-Buitrago et al [ 55 ], Ma et al [ 54 ], and Vlachogianni et al [ 60 ] respectively. Perez-Venegas et al [ 58 ] recorded a litter density of 0.001 items/m 2 on Guafo Island (Chile) while Duhec et al [ 27 ] reported 4.7 items/m 2 on Alphonse Island (Seychelles), and 3.3 items/100 m 2 was recorded by Melli et al [ 61 ].…”
Section: Discussioncontrasting
confidence: 55%
“…The data collected from the surveys were subjected to descriptive statistics (mean and range) and percentage litter compositions were estimated. To determine the abundance of litter items per unit area and relative severity of the litter pollution compared to other beaches, Litter Density (LD) and Clean Coast Index (CCI) were estimated using the formula by Ma et al [ 54 ] and Rangel-Buitrago et al [ 55 ] respectively. where LD is the density of litter items/m 2 , N is the number of litter items recorded; W and L are the Width and Length of the sampling unit (transect), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Site Description. Zhoushan Island (ZSI) is the major island in the Zhoushan Archipelago, located in the coastal area of the eastern Zhejiang province of China [52,53]. Its terrain is mainly composed of central hill range, surrounding plains, and tidal flat wetlands.…”
Section: Methodsmentioning
confidence: 99%
“…Surveys at sea can sample floating [18] and suspended debris using a manta trawl net or sample litter on the seabed [19] with submersibles or remote-operated vehicles or trawling equipment. However, most of the studies show that AMD accumulates along beaches, and hence beach surveys [20,21] are not only necessary but also represent the most common monitoring method for macro-debris. That said, beach cleanups can alter litter loads and abundance on beaches, and beach dynamics can introduce additional variables in monitoring changes in the amount and composition of plastic debris [22].…”
Section: Introductionmentioning
confidence: 99%